If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -7) + -1(4x + 2) = 0 Reorder the terms: (-7 + 5x) + -1(4x + 2) = 0 Remove parenthesis around (-7 + 5x) -7 + 5x + -1(4x + 2) = 0 Reorder the terms: -7 + 5x + -1(2 + 4x) = 0 -7 + 5x + (2 * -1 + 4x * -1) = 0 -7 + 5x + (-2 + -4x) = 0 Reorder the terms: -7 + -2 + 5x + -4x = 0 Combine like terms: -7 + -2 = -9 -9 + 5x + -4x = 0 Combine like terms: 5x + -4x = 1x -9 + 1x = 0 Solving -9 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 1x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 1x = 0 + 9 1x = 0 + 9 Combine like terms: 0 + 9 = 9 1x = 9 Divide each side by '1'. x = 9 Simplifying x = 9
| -7x+-49=-56 | | 1/2(32)(19) | | 45+15+0.75x=40+0.85x | | x^3-x^2+10x+32=0 | | 2x+3(x+5)=4x+18 | | 2x^2-1x=3x^2 | | 17a-2b+3c=126 | | 3r-3=3 | | a-3b+2c=32 | | 4/n=24/18 | | -3u+2v= | | 6a+3b+c=22 | | (x^2-4x-12)/(x^2-x-6) | | .03x+.14=.9x+.08 | | 9.25t+7=20.5t+16 | | 10t-3=t+16 | | 4u=8v | | 6=3+3h | | 5x-7-3x=15 | | N/5=8/10 | | b/3-3b/13=8/13 | | 9t/27t^-5 | | 15/3=45/n | | 32x^2-1x=0 | | x/4-x/3=5 | | 6x^2+35+25=0 | | 1.9=9.1-0.8x | | 15x=5x-9 | | 4.6+10m=6.93 | | e^3x-1=4e | | (12x-5)=(8x+15) | | 6x3/3 |